WAJAH DEMOKRASI JAKARTA DALAM POTRET INDEKS DEMOKRASI INDONESIA (IDI) - Rahmatulloh Rahmatulloh (Jurnal Ilmiah Mimbar Demokrasi, 2019)
This study aims to describe the development of local democracy in the Special Capital Region of Jakarta based on the achievement of the Indonesian Democracy Index (IDI) in the last 5 years (2013-2017). The methods used are library research, in-depth interviews, Focus Group Discussion, and analysis of news document content. The results of the study show that the achievements of the democracy index of DKI Jakarta Province occupy the highest position, compared to other provinces. In 2014 DKI Province's democracy index score reached 84.70, from a scale of 100. In 2015 the index score reached 85.32, 2016 dropped to 70.85. While 2017 reaches the highest ranking, which is 84.73. Thus, Jakarta is a national "barometer" for the achievement of democracy. The dynamics and performance of democracy in DKI Jakarta Province is strongly influenced by its position as the capital city, metropolitan city, the center of political, economic, socio-cultural life.